On the Old Uyghur Fragments of the Bāvari Narrative Housed in the Berlin Turfan Collection - Kılıç Cengiz, Ayşe (Religions, 2024)
The ancient oasis of Turfan, located on the Northern Silk Road, was a centre for interactions between the East and the West and witnessed numerous cultural, religious, and linguistic changes throughout history. A large number of texts were composed, translated, copied, and published there. One of the outcomes of these efforts is the Old Uyghur Buddhist narrative literature, parts of which have remained almost completely preserved, while a significant portion has survived as single fragments or small pieces of a fragment. For some of these texts, definitive conclusions about their original content or which work they belong to have yet to be reached. The Old Uyghur Bāvari narrative discussed in this study bears parallels, particularly in terms of themes, settings, and characters, with sections of the Pārāyaṇasūtra—known for its resemblance to the final chapter of the Sutta Nipāta, i.e., the Pārāyanavagga—as well as parts of the Maitreyasamitināṭaka and Xianyujing. This study first introduces this narrative formed by the Old Uyghur fragments preserved in the Turfan Collection of the Berlin-Brandenburg Academy of Sciences. Then, the text is transcribed and translated. Finally, the similarities and differences with other parallel narratives are analysed and presented.